Pengaruh Pendidikan Karakter Islami terhadap Moralitas Remaja: Studi Kasus di Madrasah Aliyah Manba’ul Ulum Pondok Pesantren Asshidiqiyah Jakarta - Fatihah, Nur Fitriani (Indra Institute Research & Publication, 2024)
Character education is a positive offer in overcoming the moral crisis that is currently hitting the younger generation, especially students. The younger generation will now be the mainstay and hope. Young people must really get adequate and good education which will ultimately become young people with character. One that can be used as a medium for transformation and instilling character values ​​is an Educational Institution. Internalization of character education values ​​in Educational Institutions is a must. Madrasah as one of the Islamic educational institutions in Indonesia is one of the smart solutions in developing character education values ​​both through formal and non-formal curricula, because since its inception Madrasah has shown its distinctive characteristics which are different from educational institutions in general, where the cultivation of character values It has been integrated into religious subjects which have quite a large portion. The purpose of this study is to describe the influence of character education in the Madrasah ‘Aliyah Manba’ul Ulum Asshidiqiyah Islamic boarding school on adolescent morality. The method used is qualitative with a case study method, to reveal and understand the realities that occur in depth regarding the above phenomenon. Data collection techniques are carried out using triangulation of data sources, that is interviews, observations, documentation and literature studies. Research findings in the field show that character education is implemented through two forms, that is formal curriculum and non-formal/extracurricular curriculum. Formal curriculum can be seen from the portion of religious education which is greater than general education, namely covering the Qur'an-Hadith, Aqidah-Akhlak, Jurisprudence, and History of Islamic Culture. All of that leads to the achievement of spiritual depth and noble morals as components of the basic values ​​of character education. While character education is carried out through extracurricular activities: Pakibra, Scouts, Hadroh, PMR, Taekwondo, Silat, etc.